Efficiency analysis and performance modelling of a photovoltaic system for cruise ship cabins with battery storage using direct current distribution networks - Patrick Schwager; Laura Tiede; Thomas Scholz; Kai Gehrke; Martin Vehse (International Journal of Electrical Power & Energy Systems)
Stricter regulations and increased environmental awareness are driving innovations in the maritime sector to reduce or eliminate greenhouse gas emissions. This also applies to the cruise industry. Among other things, the transition to direct current (DC) on-board grids and the increased integration of photovoltaic (PV) systems with battery storage can improve efficiency and reduce fuel consumption. The aim of this article is to describe a photovoltaic system suitable for cruise ships, its integration into an on-board DC grid and the dimensioning of the battery storage. To this end, two representative cruises in different geographical locations and seasons are considered, one in the Caribbean (March 2016) and one along the Norwegian coast (Aug-Sep 2016). The results demonstrate that the proposed solar system for a Helios class ship, operating under optimal weather conditions, delivers a daily average of 3.2 MWh and 3.8 MWh for the Caribbean and Norwegian cruises, respectively. Furthermore, a number of options were explored with regard to the integration of the PV system into the DC grid. The integration into a 350 VDC distribution grid per deck and fire zone was found to be the most advantageous. Finally, synthetic load and irradiance profiles were used to simulate ship operation within a fire zone deck to determine the size of battery storage required for that area. In order to ensure safe operation, a battery capacity of 161.4 Ah is required for the Caribbean cruise and 127.5 Ah for the Norwegian cruise.